Artist, detective, criminal: Sophie Calle as haunting flâneur in urban spaces - Bulloch, Ellie (2023)
Sophie Calle is a globally renowned figure in contemporary art, and yet she evades definition. Critics have struggled to define Calle’s artworks and artistic process since the 1970s, linking her to movements such as Conceptualism, Surrealism, and Situationism, yet falling short of an all-encompassing description. She is often connected to ideas of female madness, and contradicts what is deemed acceptable of women in art; such labels are narrow and short-sighted. I argue that it is in fact flânerie, first coined by Charles Baudelaire in 1863, which most aptly defines Calle’s artworks. When looking back on Calle’s career, it becomes apparent that she acts as a flâneur in her pieces involving movement through urban environments, following individuals as a means through which to interact with space. Calle highlights that space derives meaning from its relationship to people, but that this is also mirrored in how space can bring meaning to us. My reflection on Calle’s earlier works has stemmed from a pattern of returning and revisiting evident in her artistic process. Her engagement with flânerie highlights a desire to rediscover spaces after the passage of time, which reveals a haunting element within the role of the flâneur. This thesis seeks to situate Calle’s artistic process within the practice of flânerie, as well as conducting an analysis of the haunting nature of the flâneur. Calle’s artworks which involve movement through space and time are discussed in the thesis, such as her newest work, Les Fantômes d’Orsay (2022).